HUBUNGAN POSTUR KERJA DAN DESAIN STASIUN KERJA PADA AKTIVITAS PENJEMURAN DENGAN KELUHAN MUSCULOSKELETAL DISORDERS PADA PEKERJA LAUNDRY DI KELURAHAN TEMBALANG - IRVINA WAHYU FUADAH; Ekawati Ekawati; Ida Wahyuni (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Musculoskeletal disorders are complaints that occur in the skeletal muscles (skeletal). The design of the work station used by workers can affect the work position and comfort while working, so that the risk of workers experiencing complaints of musculoskeletal disorders will be lower. The aimed of the study to analyze the relationship between work posture and work station design on drying activities with complaints of musculoskeletal disorders in laundry workers in Tembalang Village. This study was quantitative study used cross sectional approach. The sampling technique in this study was non-probability sampling, namely used the purposive sampling technique. The sample in this study amounted to 20 workers. Based on the Exact Fisher Test, the results showed that there was no relationship between work posture and complaints of musculoskeletal disorders (p-value = 0,619) and there was no relationship between work station design and complaints of musculoskeletal disorders (p-value = 0,509). Laundry business owners and laundry workers must stretch for approximately 10 minutes between work hours to reduce complaints of musculoskeletal disorders, and improved the design of the work station height of the clothesline that is adjusted to the anthropometry of the worker's body so that workers can work safely and comfortably. Keywords : Musculoskeletal Disorders, Work station Design Clothesline, Work Posture